Mesangih: Tradisi Potong Gigi Masyarakat Hindu Bali : (Perspektif Kesehatan Gigi dan Mulut) - Damayanti, Ni Wayan Eka; Bhattacarya, Wasudewa; Ernawaty (Jayapangus Press, 2023)
Hindus consider cutting teeth known as the mesangih ceremony as an important ceremony to signify maturity and to help control lust. The procedure for the traditional tooth-cutting ceremony consists of filing the teeth three times, sharpening them, and then trimming them. This filing is on the four maxillary incisors and two left and right canines. According to published literature, traditional tools such as chisels, hammers, files, and sangian are used to carry out the ritual tradition of cutting teeth. This study aims to clarify the effect of dental filing on oral health. To achieve the research objectives, this study used a descriptive qualitative approach to describe tooth structure. The data source uses primary data, which is based on existing data from books and journals and then associated with the tradition of cutting teeth or mesangih. There are several impacts of cutting teeth on dental health, namely tooth enamel damage, gum damage, and reduced tooth function. There are several ways to avoid the impact of cutting teeth on dental and oral health including (1) need to maintain healthy teeth and mouth from before to after the implementation of mesangih; (2) organize training or procedures for the implementation of mesangih for sangging in terms of spiritual and health meaning. If this data is done, then every Hindu can carry out the tooth-cutting ceremony safely and comfortably in accordance with the rules of hereditary literature without breaking down existing health rules.